pH-sensitive nanoparticles as carriers for oral delivery of a model peptidomimetic drug / Rosa Elizabeth Valente Pereira - Valente Pereira, Rosa Elizabeth (2008)
Peptide-related drugs are usually unstable in the harsh gastrointestinal environment with poor absorption throughout the gut. The potential of anionic pH-sensitive nanoparticles to act as novel drug carriers for oral administration of such compounds was investigated using a peptidomimetic drug, cefotaxime sodium. Drug loaded nanoparticles were prepared using a pH-controlled nanoprecipitation method. Three types of nanoparticles were prepared using different grades of Eudragit polymer, namely L100, L100-55 and S100. The drug-loaded nanoparticles have a size of about 100 nm, low polydispersity, encapsulation efficiencies of more than 50%, drug entrapment and drug content between 4-5%.